Absence in context: Recontextualizing civic data, critical cartographies, and gentrification in New York City. Issue 1 (1st June 2015) - Blinder, Justin
Corporate mapping tools, such as Google Maps, have become a common lens through which we view geographical data. These tools normalize what is filtered. Such decontextualization is not mere happenstance. Numerous mapped data sets obscure and obfuscate the original context in which data were collected and, more importantly, who or what was omitted from it. In response, I draw upon the development and implementation of my art project 'Vacated', which recontextualized both the New York City government's PLUTO data set and Google Street View, to document and examine patterns of gentrification in new ways. 'Vacated' emphasizes street-level perspectives of data points to reflect on, and engage with, the larger data sets that they exist within. Contextualizing the images also renders more visible the continuous ecosystem of surveillance in which they were taken. I conclude with reflections on further possibilities for critical cartography and usable tools for everyday citizens and users.